Developing MIKE-11 Model for Water Quality Simulation in Bertam River, Cameron Highlands - Malakahmad, Dr, Amirhossein, Dr; Eisakhani, Mahdieh; Isa, M.H. (2008)
Cameron Highlands is undergoing rapid development as a popular tourist destination and an area exploited for growing of vegetables, fruits and flowers. However, it is also a mountainous area subjected to torrential tropical showers. The condition of the main rivers and its tributaries in Cameron Highlands, Ringlet lake and other constructed ponds have degraded over the years in terms of water pollution, river environment and ecosystem. Therefore, a series of measurements were carried out to identify the amounts of Dissolved Oxygen, Biochemical and Chemical Oxygen Demands, Suspended Solids, NH3-N, PO4, temperature, pH, turbidity, conductivity and Escherichia-coli. Among them in some area the amount of E-coli was 61000 MPN/100 ml and very high. MIKE-11, a one-dimensional hydrodynamic simulation program was utilized to model stream flow and water quality processing in Bertam river. The model was run in hydrodynamic, advection-dispersion and water quality modules. The results indicated that one of the most serious environmental problems for Cameron Highlands is soil erosion. In addition, it was observed that the main sources of water pollution are sewage treatment plants for hotels, rest houses and apartments.